2017
DOI: 10.1016/j.ophtha.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Femtosecond Laser Intrastromal Incision Location Using Optical Coherence Tomography

Abstract: Purpose Using optical coherence tomography (OCT) to evaluate the femtosecond laser intrastromal (IS) incisions made during cataract surgery to reduce corneal astigmatism. Design Retrospective case series. Subjects 77 eyes of 77 patients were included. Methods Paired IS incisions were created using the Catalys femtosecond laser (Abbott Medical Optics, Inc.). The planned IS incision parameters were 20% uncut anterior, 20% uncut posterior, midpoint depth of 50%, and 90° side cut angle. OCT scans were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In addition, in a previous study using OCT, we evaluated the location in the cornea of intrastromal CRIs made with the Catalys during cataract surgery. 24 The planned intrastromal incision parameters were 20% uncut anterior and 20% uncut posterior with a midpoint depth of 50%. We found that the intrastromal incision midpoint depth was significantly more anterior than the planned depth of 50%, and the locations of paired intrastromal incisions in each eye were not correlated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a previous study using OCT, we evaluated the location in the cornea of intrastromal CRIs made with the Catalys during cataract surgery. 24 The planned intrastromal incision parameters were 20% uncut anterior and 20% uncut posterior with a midpoint depth of 50%. We found that the intrastromal incision midpoint depth was significantly more anterior than the planned depth of 50%, and the locations of paired intrastromal incisions in each eye were not correlated.…”
Section: Discussionmentioning
confidence: 99%